Understanding Impulsive Buying Behaviour Among Buy Now Pay Later (BNPL) Users and its Implication for Overconsumption and The Environment - Verni Juita; Vera Pujani; Rida Rahim; Rita Rahayu (Universitas Negeri Semarang, 2023)
Over the last decade, the popularity of